Measurement invariance of the Satisfaction with Life Scale by sexual orientation - Checa, I.; Di Marco, D.; Bohórquez, M. R. (Archives of Sexual Behavior, 2022)
The Satisfaction with Life Scale (SWLS) has shown strong evidence of reliability, validity, and gender invariance, and there is some evidence of invariance across age, culture, and educational levels. So far, invariance across sexual orientation has not been studied, despite the number of works that relate well-being to sexual orientation. The SWLS should be invariant across sexual orientation to be able to compare group means. This study aimed to explore the invariance of the SWLS across sexual orientation. A non-probabilistic sample with 553 Spanish adults (208 males, 345 females; 212 heterosexuals, 182 gays, and 138 bisexuals among other sexual orientations) participated in a survey. We tested a one-factor model using confirmatory factor analysis. We tested the configural, metric, and scalar invariance of the factorial structure of the SWLS across sexual orientation with heterosexual, lesbian/gay, and bisexual groups. According to our results, the Spanish version of the SWLS shows scalar invariance across sexual orientations, allowing a valid comparison between sexual minority and heterosexual people. Moreover, in our sample, lesbian/gay and bisexual participants obtained lower scores in life satisfaction than heterosexual participants. Bisexual people obtained the lowest score in well-being compared with the other groups. Implications related to the importance of checking instrument invariance before comparing mean differences between groups are discussed.